2010
DOI: 10.7763/ijesd.2010.v1.18
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in Pyrolysis Technology for Management of Scrap Tire: a Solution of Energyand Environment

Abstract: In this study a new approach in heating system for pyrolysis technology to the recovery of liquid hydrocarbons from solid tire wastes has been developed. A fixed-bed fire-tube heating pyrolysis reactor system has been designed and fabricated considering all of the process parameters. The solid tire wastes were pyrolysed in the reactor under N 2 atmosphere. The highest liquid product yield was obtained at a pyrolysis temperature of 475 o C for feed size of 4 cm 3 and vapor residence time of 5 sec. The tire pyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 26 publications
1
29
0
6
Order By: Relevance
“…butadiena dan gas hidro karbon dengan Gross 3 Calorific Value (GCV) sekitar 37 MJ/m yang mampu untuk memenuhi kebutuhan energi untuk proses pirolisis. (Islam, et al, 2010). Sedangkan hasil yang berupa fase padat adalah arang (char).…”
Section: Kesimpulanunclassified
See 1 more Smart Citation
“…butadiena dan gas hidro karbon dengan Gross 3 Calorific Value (GCV) sekitar 37 MJ/m yang mampu untuk memenuhi kebutuhan energi untuk proses pirolisis. (Islam, et al, 2010). Sedangkan hasil yang berupa fase padat adalah arang (char).…”
Section: Kesimpulanunclassified
“…Hasil penelitian Alam (2004) menujukkan bahwa produk distilasi kering dari parutan ban yang berupa arang mempunyai nilai kalor diatas 7.000 kal/g (7.110 kal/g-7.321 kal/g), termasuk baik (Islam, et al, 2010) power (CHP)…”
Section: Kesimpulanunclassified
“…Fig. 1 presents experimental char and gas yield results from the literature, obtained from the various pyrolysis in diverse reactor configurations [9][10][11][12]. Among this data set, the range of gas and char yields was the smallest in a fixed bed reactor (FBR).…”
Section: Introductionmentioning
confidence: 98%
“…This implies that the time required for the oil shale reaction to reach the constant weight fraction would be the longest among this fuel, whereas, reaction time to achieve the same for RDF would be the shortest in this table. gas Ti re(FBR) [9] char Ti re( FBR) [9] gas PE(DTR) [11 ] char PE(DTR) [11] gas PP(FB) [10] char PP(F B) [ 10] gas P E(FB) [10] char P E(FB) [10] gas lignite(WMR) [1 2] char lignit e(WMR) [12 ] Another factor which is important for explaining the conversions of organic materials during pyrolysis is the mass balance. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Results of the study showed that heat-generating capacity of the resulting liquid fuel is 40.4 MJ/kg. The paper does not provide other characteristics compared to traditional diesel fuel, which does not allow us to talk about the high potential of fuel replacement.In the study [4], a new approach to a heating system with the use of liquid products of pyrolysis of waste tires was presented. Fuel properties of pyrolysis liquids, such as density, viscosity, the content of carbon and hydrogen, are almost comparable with commercial automobile diesel fuels.…”
mentioning
confidence: 99%